An analytic approach to the degradation of double-Schottky barrier: Theoretical prediction of VO0–Zni2+:Zni2+ as dominant mobile ion in ZnO electroceramic. (15th July 2015) - He, Jinliang; Cheng, Chenlu; Hu, Jun
Abstract : An analytic approach, aimed at characterizing the degradation properties of the double-Schottky barrier formed at the grain boundary in various electroceramics, is exhaustively described. Migration and neutralization behavior of charged defect ions is portrayed during the degradation of electrostatic potential under electrical stress. By comparing simulation results with experimental data from the aging test performed on fabricated [0 0 0 1] ZnO bicrystals, Zni 2+ from VO 0 –Zni 2+ complex donor defect is identified as the optimum candidate for the mobile ion responsible for degradation phenomena of ZnO electroceramics.